Faith. Superstar - Houser, Jody (Valiant Entertainment LLC, 2017)
Orphaned at a young age, Faith Herbert - a psionically gifted "psiot" discovered by the Harbinger Foundation - has always aspired to greatness. But now this once ordinary teenager is taking control of her destiny and becoming the hard-hitting hero she's always known she can be - complete with a mild-mannered secret identity, unsuspecting colleagues, and a day job as a reporter that routinely throws into her harms way! Well, at least she thought it would. When she's not typing up listicles about cat videos, Faith makes a secret transformation to patrol the night as the City of Angels' own leading superhero - the sky-soaring Zephyr! But flying solo is going to be tougher than she ever thought when Zephyr uncovers a deep-rooted alien conspiracy. Two-bit burglars and car thieves are one thing, but when the world needs a hero to stave off an full-blown extraterrestrial invasion, will Faith find herself in over her head or ready for her biggest challenge yet?